Corrosion Testing in Natural Waters: Second Volume 1997
DOI: 10.1520/stp11358s
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Year Field Study of The Performance of Coatings in Seawater

Abstract: The objectives of this study were to evaluate the long-term performance of various coatings on steel piles in seawater and to investigate non-destructive electrochemical corrosion testing techniques for coating evaluation in the field. Steel H piles which were 20.3 cm x 20.3 cm and 12.2 m long were installed in Buzzards Bay, Cape Cod, Massachusetts. The piles were coated with various coatings such as coal tar epoxy, polyurethane, flame sprayed zinc and aluminum. Several of the piles were left uncoated for base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Kumar et al 17 reported the corrosion performance of steel H piling after 5 years of exposure at Buzzards Bay, MA. Figure 5 shows the corrosion profiles for the two steel piles without cathodic protection or protective coatings for which R was estimated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al 17 reported the corrosion performance of steel H piling after 5 years of exposure at Buzzards Bay, MA. Figure 5 shows the corrosion profiles for the two steel piles without cathodic protection or protective coatings for which R was estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion profiles for A36 and A690 steel piles at Buzzards Bay, MA, USA (based on data reported by Kumar et al ) 17 …”
Section: Introductionmentioning
confidence: 99%